Islamic Social Finance and SDG 7: A Comprehensive Framework for Sustainable Energy Access - Sari, Putri Reno Kemala; Mutia, Galuh Ratna; Yuliati, Ni Nyoman; Suardana, I Made (Sekolah Tinggi Ilmu Ekonomi AMM, 2025)
Purpose – This study examines how Islamic social finance instruments can achieve Sustainable Development Goal 7 (SDG 7) by addressing energy poverty and climate change through sustainable energy access in developing countries. Design/Methodology/Approach – The research uses comprehensive framework analysis, integrating Islamic finance principles with sustainable development objectives. A conceptual framework examines input mechanisms (zakat, waqf, voluntary contributions), process mechanisms (resource mobilization, project development, implementation), and impact measures, supported by case studies from Indonesia, Jordan, Malaysia, and Bangladesh. Findings – Islamic social finance offers significant sustainable energy financing potential: zakat enables renewable energy infrastructure, clean energy equipment, subsidies, and training for underprivileged communities; waqf supports large-scale infrastructure through land utilization and long-term renewable projects. Case studies show successful implementations including Indonesian pesantren solar panels, Jordanian refugee camp energy solutions, Malaysian mosque solar systems, and Bangladeshi LPG programs. Challenges include limited institutional capacity, regulatory constraints, and stakeholder resistance. Originality/Value – This research provides the first comprehensive framework integrating Islamic social finance with SDG 7, offering practical guidance for leveraging zakat and waqf to address energy poverty while supporting climate mitigation, with actionable policy recommendations